Off‐therapy durability of response to entecavir therapy in hepatitis B e antigen‐negative chronic hepatitis B patients - Jeng, Wen‐Juei; Sheen, I‐Shyan; Chen, Yi‐Cheng; Hsu, Chao‐Wei; Chien, Rong‐Nan; Chu, Chia‐Ming; Liaw, Yun‐Fan (Hepatology (Baltimore, Md.), 2013)
The optimal duration of nucelos(t)ide analog (Nuc) treatment in hepatitis B e antigen (HBeAg)‐negative patients with chronic hepatitis B virus (HBV) infection is unknown. The Asian Pacific Association for the Study of the Liver (APASL) guidelines recommend that treatment can be discontinued if undetectable HBV‐DNA has been documented on three occasions ≥6 months apart. This study aimed to test this stopping rule in HBeAg‐negative chronic hepatitis B (CHB) patients treated with entecavir (ETV). Ninety‐five patients (39 cirrhosis) were treated with ETV for a median of 721 (395‐1,762) days before stopping therapy and were then monitored with serum HBV DNA and alanine aminotransferase (ALT) at least every 3 months. Within 1 year after stopping ETV therapy, “clinical relapse” (an episode of ALT elevation >2 × upper limit of normal plus HBV‐DNA >2,000 IU/mL) occurred in 43 (45.3%) of the 95 patients. Of the 39 cirrhosis patients, 17 (43.6%) relapsed and one (2.6%) developed decompensation. The median duration until relapse was 230 days (74.4% >6 months). Logistic regression analysis showed that baseline HBV‐DNA ≤2 × 105 IU/mL was the only significant independent factor for sustained response. The 1‐year relapse rate was 29% in patients with a baseline HBV DNA ≤2 × 105 IU/mL versus 53% in those with HBV DNA >2 × 105 IU/mL (P = 0.027). For the latter, consolidation therapy >64 weeks reduced the relapse rate to 33.3% in patients without cirrhosis. Conclusion: With an overall 1‐year relapse rate of 45% and 29% in those with a baseline serum HBV DNA ≤2 × 105 IU/mL, the APASL stopping rule for HBeAg‐negative CHB patients with proper off‐therapy monitoring is adequate even in patients with cirrhosis. Consolidation therapy >64 weeks seems more appropriate for those with higher baseline HBV DNA. (Hepatology 2013; 58:1888–1896)